ENTREPRENEURIAL FORMATION IN TVET: A SEM ANALYSIS OF KNOWLEDGE, FAMILY ENVIRONMENT, AND SPIRIT ON SELF-EFFICACY AND INTEREST AMONG COMPUTER AND NETWORK ENGINEERING STUDENTS - Arfandi, Anas; Nurfauziah, Nurfauziah; Purnamawati, Purnamawati; Pechinthorn, Komm (UNIVERSITAS NEGERI SURABAYA, 2025)
Unemployment is a serious problem, especially for young people graduating from vocational schools. Vocational education and training (TVET) is a strategic solution to prepare young people to become job seekers and creators. However, the number of vocational school graduates who become entrepreneurs is still low. This indicates a gap between the school entrepreneurship education and students' motivation to become entrepreneurs. This study aims to analyze the influence of entrepreneurship knowledge, family environment, and entrepreneurial spirit on entrepreneurial interest, with self-efficacy as a mediating variable, among students of the Computer and Network Engineering Vocational High School in Makassar. This study uses a quantitative approach with an ex post facto method on 178 respondents, and the data is analyzed using SEM-PLS. The study results show interesting findings: entrepreneurial knowledge does not significantly affect entrepreneurial interest, while family environment and entrepreneurial spirit have a positive and significant effect. Self-efficacy was proven to strongly mediate between psychological factors (entrepreneurial spirit) and social factors (family environment) to entrepreneurial motivation. Theoretically, this study provides evidence that with these research results, Bandura's self-efficacy theory in vocational education can confirm that self-efficacy is the key to shaping students' entrepreneurial behavior. Practically, the results of this study emphasize the importance of project-based and real-life entrepreneurial learning that builds students' confidence in entrepreneurship, as well as the important role of the family in supporting students to become entrepreneurs. These findings provide important insights for educators and policymakers in strengthening entrepreneurial education in vocational high schools.